The visual poetry in the film criticism of Ángel Fernández-Santos (2015)
Very often, it isZunzunegui, S. (1996ntify these principles. It is a term that, within his evaluative arguments, constitutes one out of three great stylistic strategies which, due to their difficulty and complexity when applied in the filmmaking, the critic tends to associate with the highest levels of the aesthetic quality. The other two strategies are the ‘transparency/depth dichotomy’ and the ‘expressive paradoxes’. In this paper, we focus on the film aesthetic patterns of Ángel Fernández-Santos in order to extract from his reviews only the definition, features and typologies of the visual poetry concept where it is clearly used. Those writings come from his journalist career in the newspaper El País (1982-2004), and they are devoted to analyse a range of audiovisual productions of different periods and styles; but before that, we will make reference to the origins and the application of the visual poetry concept in the legacy of the film theory and criticism with the aim of highlighting the influences that, (in this field) determine the aesthetic scope in the film reviews of Fernández-Santos. © 2015 Communication & Society.